Fungal Pathogens Associated With Roselle (Hibiscus Sabdariffa) In Penang, And Controls - Eslaminejad, Touba (2011)

(untitled)
The main objective of this study was to identify and characterize fungal pathogens associated with Roselle diseases in Penang, and to study their control. A total of 200 fungal isolates were obtained from 90 samples of symptomatic Roselle tissues. The isolates were identified based on cultural and morphological characteristics, as well as their pathogenicity. The fungal pathogen most frequently isolated was Phoma exigua (present in 45 % of the samples collected), followed by Fusarium nygamai (25 %), Rhizoctonia solani (19 %) and F. camptoceras (11 %).